The linkage between board of directors characteristics, distinct business environments and organizations financial performance - Haron, Razali; Ibrahim, Khairunisah; Muhamad, Nordin (2009)
This study investigates the often claimed linkage between board of directors attributes and corporate performance in the construction and technology sectors between financial year 2000 and 2001. More specifically, this study examines the impact of board of directors composition and control function on firm performance. The researchers further explore the differences in board diversity ratio and category of auditing firms within each sector with regards to company financial performance. Correlation and paired sample t-test statistic is employed to test the mean differences of variables between the two sectors. To further explore the differences in board diversity ratio and the categories of auditing firms within each sector with regards to the company’s financial performance, the study employs multivariate analysis of variance (MANOVA). In conclusion, there are certain aspects of board attributes and control functions that differ between the two sectors, and these significantly influence firm performance. This finding thus confirms the differences in business nature and environment between the two sectors.